A New Model of Diarrhea with Spleen-Kidney Yang Deficiency Syndrome. (30th September 2018) - Zhu, Jiajie; Liu, Shan; Guo, Yu; Hou, Liwei; Su, Xiaolan; Li, Yijie; Han, Boyu; Liu, Dengke; Wang, Qingguo; Chen, Jiande JD; Wei, Wei
Abstract : Objective . The aim of this study was to examine a new method to create a rat model of diarrhea with spleen-kidney yang deficiency syndrome. Methods . A senna leaf (Folium sennae) decoction was made in 3 concentrations of 1.0, 0.5, and 0.25 g/mL. Rats were randomly divided into 4 groups: the control (C)-, high (H)-, middle (M)-, and low (L)- dose groups. The groups received saline, 1.0, 0.5, or 0.25 g/mL senna leaf decoction, respectively, for 4 weeks. Body weight monitoring, food consumption, water intake, defecation frequency, stool Bristol score, weight-loaded forced swimming test, forelimb grip strength test, D-xylose absorption test, serum cortisone, adrenocorticotropic hormone (ACTH), 24 h urine 17-hydroxycorticosteroid (17-OHCS), and histopathological detection were conducted to assess the success of the senna leaf decoction-induced model. Results . This study showed that the senna leaf decoction could induce diarrhea and dose-dependently slow body weight growth, reduce food consumption, and increase water intake, stool Bristol score, and defecation frequency. Statistical differences were found between groups H and M in rectal temperature, weight-loaded forced swimming time, forelimb grip strength, and serum cortisone. The D-xylose absorption test also showed dysfunction of intestinal absorption in groups H and M. The serum cortisone and 24 h urine 17-OHCS were significantly reduced in group H. Conclusions . Gastric gavage of 10 mL/kg of body weight of a high concentration of a senna leaf decoction (1.0 g/mL) for 4 weeks was used to create a rat model of diarrhea with spleen-kidney yang deficiency syndrome.